2021
DOI: 10.12973/ijem.7.4.603
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Purpose in Life in College Students: An Assessment of Invariance Properties by College Year and Undergraduate School

Abstract: <p style="text-align: justify;">Purpose in life is a key construct in the development of young adults, particularly college students. There are many instruments measuring sense of purpose in life, but few studies have examined their measurement properties among college students. The current study compares the measurement invariance properties of the Purpose in Life (PIL) scale and the Claremont Purpose Scale (CPS) across college year and undergraduate school. Using both a unidimensional and a two-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…To be successful in the large-scale educational space, today's competitive universities must be partners in the digital context (Anghel et al, 2021). The European experience confirms the relevance of some educational cases providing the application of digital platforms in traditional education.…”
Section: Research Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…To be successful in the large-scale educational space, today's competitive universities must be partners in the digital context (Anghel et al, 2021). The European experience confirms the relevance of some educational cases providing the application of digital platforms in traditional education.…”
Section: Research Resultsmentioning
confidence: 81%
“…At the same time, Kirshner (2021) characterized the transformation of the education system due to the challenges of the Covid-19 pandemic. Anghel et al (2021) investigated the characteristics of becoming a graduate student. Also Ben-Amram & Davidovitch (2021), with a thorough case study, identified the formation of digital competencies in students, while also characterizing the attitudes of students and parents towards distance learning.…”
Section: Research Aim and Research Questionsmentioning
confidence: 99%
“…The CPS was adapted and validated in other countries and languages, and showed an e cient method for measuring purpose with strong psychometric properties demonstrated in Western studies (Bronk et al, 2018;Veazey, 2020) and Asia (Yuliawati, 2021;Wang et al, 2022). The CPS also demonstrated measurement invariance across both college year and undergraduate school indicating that the CPS can be reliably used to compare purpose in life among college students across different years of study and across different schools (Anghel et al, 2021). As a result, the CPS can be considered a reliable instrument for assessing PIL's element, beyond-the-self, potentially enhancing the empirical study of this concept.…”
Section: Introductionmentioning
confidence: 94%
“…The student is given the opportunity to choose between a professional orientation and a theoretical research orientation. The latter is offered to students who are to enter a doctoral program (Anghel et al, 2021).…”
Section: Research Focusmentioning
confidence: 99%